A STUDY OF THE IMPACT OF BRAND VALUE OF NEW ENERGY AUTOMOBILE INDUSTRY ON CONSUMERS’ PURCHASE INTENTION, WITH BRAND PERSONALITY AS AN INTERMEDIARY VARIABLE - Wu, Yuxin (Journal of Buddhist Education and Research (JBER), 2022)
With the world's continuous attention to energy conservation and environmental protection, the era of new energy vehicles is coming, and all over the world are actively developing the new energy vehicle industry. As the world's largest automobile consumer country, China pays more attention to vigorously developing the new energy vehicle industry. This research is based on the brand construction of new energy vehicle enterprises, to brand value, the relationship between brand personality and consumer purchase willingness as the research problem, through the questionnaire survey of data collection, analysis, finally verify the hypothesis model, brand personality plays an intermediary role between brand value and consumer willingness to buy. At the same time, the research results found that the functional value of the brand value had the most significant effect on the purchase intention; the "courage", "benevolence" and "Happy" had the most significant effect on the purchase intention. In the study of the intermediary effect, the brand value has the most significant effect on the purchase intention through the three dimensions of "brave", "Benevolence" and "Happy".